Metodologi penelitian kualitatif / M. Djunaidi Chony & Fauzan Almanshur ; editor, Rina tyas Sari. - DJUNAIDI CHONY, M, 1944; Rina Tyas Sari; Fauzan Almanshur, 1973 (Ar-Ruzz Media, 2012)
386 hlm. : ilus ; 25 cm (3 eks.)